La vulneración del derecho humano a la integridad personal de las personas privadas de libertad en el marco de la emisión de los Decretos Ejecutivos nro. 110 y 111 del año 2024 en el Centro de Privación de Libertad Chimborazo nro. 1 y nro. 3. - Chávez Sánchez, Doménica (2024)
This research report analyzes the possible violation of the human right to personal integrity of persons deprived of liberty in Ecuador, specifically in Deprivation of Liberty Centers No. 1 and 3 of Chimborazo, as a result of the issuance and subsequent implementation of Executive Decrees No. 110 and 111 of 2024. These decrees were issued in a context of increased violence in Ecuador, this response triggered the declaration of an Internal Armed Conflict or Non-International Armed Conflict, through which joint interventions by the Armed Forces and the National Police have been authorized in deprivation of liberty centers nationwide. The study explores how these interventions, instead of protecting human rights, have resulted in complaints of acts of torture and cruel, inhuman and degrading treatment, which are currently being processed through the intervention of the Attorney General's Office, an institution that has received the alerts issued by human rights institutions such as the Ombudsman's Office. Through a legal and human rights analysis, compliance with basic standards of International Humanitarian Law and the responsibility of the Ecuadorian State in guaranteeing the personal integrity of persons deprived of liberty in the province of Chimborazo are evaluated. The conclusions reveal a significant violation of the right to personal integrity in the framework of these operations, underlining the urgent need to reform security policies and guarantee effective mechanisms for social rehabilitation. This final research report proposes that the State comply with its international obligations in the area of human rights.